Turning economic growth into nutrition-sensitive growth - Headey, Derek D. (International Food Policy Research Institute, 2011)
There is a growing consensus that reducing childhood malnutrition is a critically important goal, but there is far less agreement on what strategies can best achieve the goal. Are more nutrition-specific interventions required, such as food/nutrient supplements or training and education programs? Or does the answer lie in broader social developments such as rising incomes, increased food security, and better access to education, health, infrastructure, and family planning services? These factors can all be seen as facets of integrated socioeconomic growth, but stakeholders rightly point to examples of economic growth leading to little or no reduction in childhood malnutrition. This does not rule out an important role for economic growth, however, provided that its benefits translate into increased food availability, reductions in poverty, and broader social development—that economic growth is “nutrition-sensitive.